2020
DOI: 10.3390/ijms21175986
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Dysregulation and Mitochondrial Dysfunction in Neurodegenerative Diseases

Abstract: Neurodegenerative diseases are debilitating and currently incurable conditions causing severe cognitive and motor impairments, defined by the progressive deterioration of neuronal structure and function, eventually causing neuronal loss. Understand the molecular and cellular mechanisms underlying these disorders are essential to develop therapeutic approaches. MicroRNAs (miRNAs) are short non-coding RNAs implicated in gene expression regulation at the post-transcriptional level. Moreover, miRNAs are crucial fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 170 publications
2
57
0
Order By: Relevance
“…Excessive oxidative stress induces mitochondrial impairment and causes a decrease in ATP production, altered calcium homeostasis and a further increase in reactive oxygen species production. These events lead to DNA, lipid and protein damage and long-term increase can cause mitochondrial DNA mutation, ultimately progressing the disease severity [46] Moreover, this oxidative stress may aggravate a vicious and interminable cycle of neuro-inflammation, which further promotes oxidative stress [47,48]. Previous studies also substantiate ICV-STZ-induced decreased GSH and increased MDA levels in the cortex and hippocampus [8].…”
Section: Discussionmentioning
confidence: 85%
“…Excessive oxidative stress induces mitochondrial impairment and causes a decrease in ATP production, altered calcium homeostasis and a further increase in reactive oxygen species production. These events lead to DNA, lipid and protein damage and long-term increase can cause mitochondrial DNA mutation, ultimately progressing the disease severity [46] Moreover, this oxidative stress may aggravate a vicious and interminable cycle of neuro-inflammation, which further promotes oxidative stress [47,48]. Previous studies also substantiate ICV-STZ-induced decreased GSH and increased MDA levels in the cortex and hippocampus [8].…”
Section: Discussionmentioning
confidence: 85%
“…Aβ-induced cytotoxicity is linked to oxidative stress [ 11 , 12 ], perturbation of intracellular calcium homeostasis [ 13 ], overproduction of tumor necrosis factor-α (TNF-α) [ 14 ], mitochondrial dysfunction [ 11 , 12 , 15 ] and apoptosis [ 10 , 16 , 17 ]. Determining the underlying mechanism of neuronal cell death induced by Aβ is an essential step in treating AD.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Catanesi et al (2020) reported that miR-98 endorses Aβ formation by targeting insulinlike growth factor 1 implying its pathological role in AD. miR-15a, miR-34a, miR-126, miR-181a, miR-210-3p, miR-425, and miR-424 remained upregulated in AD, which can endorse structural and functional loss of mitochondria and found to play pathological roles in AD (Catanesi et al, 2020;John et al, 2020). miR-27a and miR-101 negatively regulate mitophagy, which remains upregulated in AD (John TA B L E 1 Role of different types of miRs on mitochondrial dynamic proteins miRNAs Functions miR-499 Suppression of calcineurin-mediated dephosphorylation of Drp1 (Wang et al, 2011) miR-140 Promotes mitochondrial fission and Apoptosis by downregulating Mfn1 miR-761 Downregulation of Mitochondrial Fission Factor (MFF) (Long et al, 2013) miR-34b/c Downregulation of miR-34b/c leads to reduced expression of DJ1 and Parkin-promoting mitochondrial fragmentation in Parkinson's disease (Minones-Moyano et al, 2011).…”
Section: Role Of Mirs In Mitochondrial Biogenesis Dynamics and MImentioning
confidence: 95%
“…miR-98 can mitigate mitochondrial dysfunctions and reduce Aβ formation through preventing Notch pathway via targeting hairy and enhancer of split (Hes)-related with YRPW motif protein 2 (HEY2) (Amakiri et al, 2019). In contrast, Catanesi et al (2020) reported that miR-98 endorses Aβ formation by targeting insulinlike growth factor 1 implying its pathological role in AD. miR-15a, miR-34a, miR-126, miR-181a, miR-210-3p, miR-425, and miR-424 remained upregulated in AD, which can endorse structural and functional loss of mitochondria and found to play pathological roles in AD (Catanesi et al, 2020;John et al, 2020).…”
Section: Role Of Mirs In Mitochondrial Biogenesis Dynamics and MImentioning
confidence: 99%
See 1 more Smart Citation